STRATEGI PENGELOLAAN DESA WISATA JAMU KIRINGAN, KECAMATAN JETIS, KABUPATEN BANTUL - Suharto Suharto (Journal of Tourism and Economic, 2019)
The research was conducted to know development of tourism after Jamu Kiringan rural tourism was formed and strategy of management also to know the obstacles in management process. The research was conducted in Jamu Kiringan rural tourism on December 2018 to January 2019. Data were obtained from interview with 4 informants consist of informants of rural tourism management, informant of village official, informant of society who join to tourist activity and informant of society who not join to tourism activity. The research was also obtained from questionnaires that have been given a Likert Scale rating to 30 respondents. The sampling was done by Purposive Sampling technique. The analysis methods used in this research are data analysis from Miles and Huberman (reduction, display and conclusion drawing or verification), analysis of IFAS EFAS and SWOT matric analysis. The result of this research show calculation value of internal factors x is 0, 0857 and external factors y is 1, 4171. From the calculation of IFAS EFAS table show the x value and y value is positive same, so the position in quadrant 1 in SWOT analysis. It mean the position of Jamu Kiringan rural tourism profitable that have strength and opportunity, so it can cover weakness and threat and also take effect in management strategy in Jamu Kiringan rural tourism. In quadrant 1 produce Strength and Opportunity strategy (SO) consist of make Jamu Kiringan to be the best rural tourism in Bantul Regency with main attraction is Jamu, manage attraction products to be tour package with a varied composition, make a great herbal garden that contains various types of herbal plants, increase export quantity and international cooperation network and increase tourist visits because of the ease of access so that has an impact on the village economy.